ASASSN-15no: the Supernova that plays hide-and-seek. Issue 1 (27th February 2018) - Benetti, S; Zampieri, L; Pastorello, A; Cappellaro, E; Pumo, M L; Elias-Rosa, N; Ochner, P; Terreran, G; Tomasella, L; Taubenberger, S; Turatto, M; Morales-Garoffolo, A; et al.
Abstract: We report the results of our follow-up campaign of the peculiar supernova ASASSN-15no, based on optical data covering ∼300 d of its evolution. Initially the spectra show a pure blackbody continuum. After few days, the HeI λλ 5876 transition appears with a P-Cygni profile and an expansion velocity of about 8700 km s −1 . Fifty days after maximum, the spectrum shows signs typically seen in interacting supernovae. A broad (FWHM ∼ 8000 km s −1 )  Hα  becomes more prominent with time until ∼150  d after maximum and quickly declines later on. At these phases  Hαstarts to show an intermediate component, which together with the blue pseudo-continuum are clues that the ejecta begin to interact with the circumstellar medium (CSM). The spectra at the latest phases look very similar to the nebular spectra of stripped-envelope SNe. The early part (the first 40 d after maximum) of the bolometric curve, which peaks at a luminosity intermediate between normal and superluminous supernovae, is well reproduced by a model in which the energy budget is essentially coming from ejecta recombination and 56 Ni decay. From the model, we infer a mass of the ejecta Mej  = 2.6 M⊙ ; an initial radius of the photosphere R0  = 2.1 × 10 14  cm; and an explosion energy Eexpl  = 0.8 × 10 51  erg. A possible scenario involves a massive and extended H-poor shell lost by the progenitor star a few years before explosion. The shell is hit, heated, and accelerated by the supernova ejecta. The accelerated shell+ejecta rapidly dilutes, unveiling the unperturbed supernova spectrum below. The outer ejecta start to interact with a H-poor external CSM lost by the progenitor system about 9–90 yr before the explosion.